Implementasi Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Listrik Statis - Nurul Syamsiah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
Physics is one of the subjects studied by students, especially students in the Department of Natural Sciences. The fact that Physics is a subject that is difficult for students to understand. Students complain about how difficult it is to understand physics, so that it impacts on the low results of student learning evaluations. Based on the results of interviews with teachers in the field of study and initial observations at SMAN 8 Pandeglang, especially class XII-IPA 3 found several causes of the students' lack of understanding of physics subjects, one of which is the lack of student participation during the learning process, which causes students to be less motivated in learning physics that has an impact on the low student learning evaluation results Based on the above problems, it is necessary to implement a learning model that emphasizes the maximum student participation during the learning process so that it can improve student learning outcomes and can train or grow students' science process skills. One of them is a guided inquiry learning model. This research uses the Classroom Action Research (CAR) method whose model was developed by Kemmis and Mc Taggart which consists of several continuous cycles. the results showed that all indicators that have been determined as successful assessments (PTK) with the guided inquiry model were successful